The Impact of Consumers’ Dynamic Browsing Modes on the Effect of In-Feed Native Advertising - Xiao, Bangming; Zhang, Hao (Frontiers in Psychology, 2022)
As an emerging form of online display advertising, in-feed native advertising is increasingly employed in online news feed platforms. While many advertisers have largely embraced this new advertising format, the current research is full of controversy on whether the more native, the better the effect of in-feed native advertising. Based on recent studies on this emerging topic, the authors explore the effective in-feed native advertising persuasion strategies based on consumers' dynamic online browsing modes. In study 1, the authors conducted an archived-data analysis (in co-operation with Baidu company) to show that in-feed native advertising persuasion (implicit vs. explicit) should be matched to consumers' real-time news feed browsing modes (convergent vs. divergent) to achieve better ad performance. In study 2, the authors further explain why consumers under different browsing modes respond differently (the mediation effect of self-agency vs. external agency) to specific in-feed native advertising persuasion. Our work explores the boundaries of agency theory from a dynamic perspective and helps practitioners conduct real-time and effective targeting strategies in in-feed native advertising.